2013
DOI: 10.1148/radiol.13121702
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Carotid Atherosclerosis: Short-term Natural History of Lipid-rich Necrotic Core—A Multicenter Study with MR Imaging

Abstract: Serial MR imaging of the carotid artery allowed observation of changes in LRNC over a short follow-up period and demonstrated the complexity of plaque progression patterns related to tissue composition. LRNC progression may be influenced not only by clinical characteristics, but also and to a large extent by plaque characteristics such as IPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 45 publications
3
36
1
Order By: Relevance
“…With such a design, reader variability in drawing contours is reduced, and artifacts from unsuppressed flow or partial volume are more consistently interpreted. Consequently, biological differences on plaque composition between serial images can be detected more readily [68]. Additionally, our data indicated that smaller LRNCs were associated with lower kappa and larger CV, which was not shown in previous studies of smaller sample size.…”
Section: Discussioncontrasting
confidence: 44%
“…With such a design, reader variability in drawing contours is reduced, and artifacts from unsuppressed flow or partial volume are more consistently interpreted. Consequently, biological differences on plaque composition between serial images can be detected more readily [68]. Additionally, our data indicated that smaller LRNCs were associated with lower kappa and larger CV, which was not shown in previous studies of smaller sample size.…”
Section: Discussioncontrasting
confidence: 44%
“…Natural history studies showed that most ischemic strokes due to carotid atherosclerosis occurred in the presence of IPH, whereas the short-to-midterm stroke risk in the absence of IPH was minimal (6,27). Thus, the potential effect of IPH-targeted diagnosis and therapeutics on the residual cardiovascular risk under the current standard of care is considerable (28). …”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Xu et al 12 reported that the occurrence rate of high-intensity signal was significantly different between symptomatic and asymptomatic MCAs. In our study, MR-positive IPHs within BA plaques were found in 30 patients (42.3%).…”
Section: Discussionmentioning
confidence: 99%